Experimental Study of Vapor-Liquid Equilibrium and Optimization of Pressure-Swing Distillation for Methanol-Dimethyl Carbonate Binary System - Cho1, Jaesuk; Mi Kim2, Yu; Noh3, Jaehyun; Sun Kim1, Dong; Cho1, Jungho (Asian Journal of Chemistry, 2014)
The mixture of methanol and dimethyl carbonate is characterized by an azeotropic point, thus, it is impossible to separate the azeotrope into respective high-purity products by general distillation. Herein, the separation of a methanol-dimethyl carbonate mixture via pressure-swing distillation was evaluated based on modeling and optimization of the separation process to obtain high-purity dimethyl carbonate. Currently, no experimental data on vapor-liquid equilibrium of methanol-dimethyl carbonate system is available in existing references. And even PRO/II, Aspen Plus, and ChemCAD simulation programs do not include a built-in binary interaction parameter of thermodynamic model of methanol-dimethyl carbonate system for accurate calculation. Therefore, the vapor-liquid equilibrium of the methanol-dimethyl carbonate binary system was experimentally evaluated under low-pressure and atmospheric pressure conditions and the binary interaction parameters were deduced from the non-random two-liquid model regression using the experimental data. The obtained binary interaction parameters were applied in modeling of the pressure-swing distillation process. Reboiler heat duty values from simulations under high-low pressure and low-high pressure configuration processes were compared and the process was optimized to minimize the heat duty.